Postdischarge Light-Intensity Physical Activity Predicts Rehospitalization of Older Japanese Patients With Heart Failure. Issue 3 (May 2018) - Miyahara, So; Fujimoto, Naoki; Dohi, Kaoru; Sugiura, Emiyo; Moriwaki, Keishi; Omori, Taku; Takeuchi, Tetsushiro; Kumagai, Naoto; Nakamori, Shiro; Yamada, Norikazu; Ito, Masaaki
Abstract : Purpose: Regular physical activity (PA) is recommended for patients with heart failure (HF). However, the clinical and social characteristics of older HF patients with low-level PA and the impact of light-intensity PA on 6-mo postdischarge adverse cardiovascular events are still unclear. Methods: Forty-one older patients who had been admitted because of decompensated HF (American College of Cardiology [ACC]/American Heart Association [AHA] HF classification stage C/D: 76 ± 5 y) were prospectively enrolled. Light-intensity (1.5-2.9 metabolic equivalents [METs]) and moderate-intensity (≥3 METs) PAs were determined by triaxial accelerometry for at least 7 d postdischarge. Six-min walk distance and 36-item Short Form questionnaire (SF-36) score were evaluated at discharge. HF patients were stratified into either the HFPA-high or HFPA-low group according to median daily PA. Twenty-nine older ACC/AHA stage A/B outpatients (HF-risk), who were at risk for HF but no symptoms of HF had developed, also completed these assessments. Clinical predictors for 6-mo postdischarge HF rehospitalization were assessed. Results: HF patients were anemic and less active. HFPA-low patients were less likely to engage in household work, took fewer steps, and had less light and moderate-intensity PA than HFPA-high patients. There were no differences in 6-min walk distance, SF-36 score, or left ventricular ejection fraction between HFPA-low and HFPA-high patients. Postdischarge PA, especially light-intensity PA, was independently associated with HF rehospitalization. Conclusion: Low volume of PA postdischarge, especially at 1.5 to 2.9 METs, predicts 6-mo postdischarge HF rehospitalization in older HF patients. Abstract : Physical activity (PA) was measured using a triaxial accelerometer in patients with heart failure (HF) after discharge as well as in cardiovascular outpatients with no HF. Patients were stratified into the low (HFPA-low) and high PA (HFPA-high) groups. During the 6-mo follow-up, HFPA-low patients had the highest risk for HF rehospitalization.